Physicochemical characteristics of stingless bee honey from heterotrigona itama / Hendrie Johann Muhamad Ridzwan … [et al.] - Muhamad Ridzwan, Hendrie Johann; Ismail, Nur Syamimi; Yusop, Mohamad Amir Shah; Wan Razali, Wan Aizuddin; Mohammed, Anisah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Stingless bee honey from Meliponini species is less common than honey produced by honey bee from Apis species. However, Meliponini consists of more than 50 species than Apis. This study aims to investigate the physicochemical characteristics of Malaysian stingless bee honey from Heterotrigona itama species. The samples of stingless bee honey were collected from UiTM Jengka, Pahang. The honey produced by Heterotrigona itama was selectively taken from five different logs. The physicochemical parameters tested were pH, ash content, acidity value, colour intensity, and moisture content. The pH of the stingless bee ranging between 3.32±0.01 to 3.60±0.01. The colour of the honey is in the range of light amber to extra light amber. The ash content and acidity value of the stingless bee honey samples ranging from 0.127±0.061 g/100g to 0.413±0.022 g/100g and 109±7.81 meq/kg to 135±8.66 meq/kg, respectively. The moisture content value ranging from 23±0.50 % to 26.83±0.29 %. Except for the ash content, the physicochemical characteristic result of the honey obtained from different logs was nearly similar.